"I Was Following Orders": An Ancient Greek Archetype of Modern War Crime Legislation*. Issue 1 (17th February 2018) - Kucharski, Janek
Abstract: This article discusses Lysias' Against Eratosthenes as an ancient Athenian instance of the superior orders plea, a line of defence made notorious during the Nuremberg trials, which in turn became the cornerstone of modern war crime legislation. Whereas the pre-Nuremberg jurisdiction largely embraced the principle of superior responsibility, whereby a subordinate executing criminal orders was not to be held liable for them, the trials of the Nazi war criminals brought about a complete reversal of this doctrine. While remaining faithful to the spirit of the Nuremberg jurisdiction, the subsequent legislative acts (which dealt, among other things, with the atrocities committed in the former Yugoslavia) sought to further elaborate its underlying principle of absolute liability, in order to precisely determine the question of guilt and innocence. I argue that despite the close relationship between modern legal systems and Roman law, which fully embraced the doctrine of superior responsibility, it is in the juridical thought of ancient Athens that one finds the archetype of contemporary war crime legislation.